CORRELATES OF ADEQUACY OF RETIREMENT BENEFITS AMONG THE OLDER PERSONS IN NIGERIA - Olukorede, Wahab Elias; Isiugo-Abanihe, U. C. (European Scientific Journal, ESJ, 2012)
Background–It is unknown how socio-demographic variables impact on adequacy of gratuity among the older persons in Nigeria. This has become essential in order to improve the preparation for old age among Nigerians. Reliable information is also required to formulate comprehensive social security system for the elderly. Methods - Quantitative data was collected through individual-based questionnaire. Multi-stage sampling procedure was employed to select local government areas, enumeration areas and individuals for the study. In all, 810 respondents were interviewed. Findings - In the female model, the result indicates that aged 60-64 years are 62 percent less likely to, those aged 65-69 are 72 percent less likely to have reported adequate gratuity than those aged 70 years and above. As regards education, those with primary education are 95 percent less likely to report adequacy of gratuity than those with secondary education. With respect to religion, while Christians are 1.3 times more likely to, Muslims are 1.4 times more likely to report adequate gratuity than those who are adherents of African traditional religion. Finally, while those with 1-3 children are 3.4 times more likely to, those with 4-6 children are 1.9 times more likely to report adequate gratuity than those with seven or more children. Conclusion - The idea that old-age security and well being in Nigeria should remain the primary responsibility of the family is untenable. Government must assume the primary responsibility in a partnership in which the family also continues to play a significant role.